2019
DOI: 10.1177/1541204019883922
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Changes in Youth Offenders’ Risk Profiles: A Latent Transition Analysis

Abstract: This study examined youth probationers’ risk profiles at the start and the end of probation and the types of transition in risk profiles over time. It further identified the association between the transition types, their adverse family background as well as their probation completion status. Using a sample of 935 youth probationers in Singapore, a latent transition analysis was conducted based on seven dynamic domains captured in the Youth Level of Service/Case Management Inventory 2.0. Based on the risk prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…Similar to prior studies, this study found that while the majority (78%) of the individuals remained within their same group at intake and exit, some youth did switch risk profiles between timepoints (Hilterman et al, 2019; Xu et al, 2020). In this study, the probability of staying in the same group ranged from .67 to .97.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar to prior studies, this study found that while the majority (78%) of the individuals remained within their same group at intake and exit, some youth did switch risk profiles between timepoints (Hilterman et al, 2019; Xu et al, 2020). In this study, the probability of staying in the same group ranged from .67 to .97.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with prior studies, there was a group of youth who were overall low risk and a group of youth who were overall high risk across many domains (Brown et al, 2021; Hilterman et al, 2019; Lee & Taxman, 2020; Onifade et al, 2008; Schwalbe et al, 2008; Xu et al, 2020). Consistent with the RNR framework, the youth in the Low Risk group spent the least amount of time on probation and most of these youth exited probation still low risk.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…With the support of the Safe Futures funds, the probation services and mentoring programs for the youth are introduced in some states, as well as in the specialized centers (Morley et al, 2000). The youth rehabilitation service conducts ample activities in USA targeting the reduction in risk of the repletion of crimes committed by the minors and held accountable previously (Xu et al, 2019). that manifests particular significance of the interests of children and adolescents, and the need to nationwide and steadily take into account the priority of the interests of children.…”
Section: Discussionmentioning
confidence: 99%